Factors predicting screen time related to physical and behavioural complaints in primary school children - Ting, Siew Leng; Rosalia, Saimon; Md Mizanur, Rahman; Rasitasam @ Razitasham, Safii; Ho, Siat Lian; Nancy, John; Lim, Lik Thai; Nazirin, Arsad (2020)
Background and objective: Physical and behavioural problems from extended usage of electronic devices are issues among primary school children. This study is aimed to investigate the prevalence of physical and behavioural complaints arising from the electronic device usage and to identify the potential factors that predicted the complaints.